Hypertrophic Herpes Simplex—Pseudocarcinoma. Issue 6 (November 2018) - Parker, Laura R.; Stanford, Brian J.; Nahass, Ronald G.
Abstract : Abstract: Individuals with human immunodeficiency virus (HIV) are commonly coinfected with herpes simplex virus type 2 (HSV-2) and human papilloma virus (HPV). Herpes simplex virus type 2 in HIV-infected individuals can present as atypical hypertrophic lesions, and HPV-induced malignant lesions can present as atypical hyperkeratotic lesions. We report a case of an atypical hypertrophic HSV-2 lesion in a well-managed HIV-infected male with a history of nonmalignant Buschke-Lowenstein tumor (giant condyloma) of HPV and squamous cell carcinoma of the scrotum. Determining the definitive diagnosis of hypertrophic HSV-2 in this patient was confounded by the macroscopic clinical presentation of the proliferative lesion and by the patient's history of squamous cell carcinoma, in the same perineal region. Knowledge of hypertrophic HSV-2 is imperative when considering the etiologic agent of anogenital lesions in HIV-infected individuals. Abstract : This case highlights the difficulty of differentiating common anogenital proliferative diseases that have similar clinical presentations in HIV-infected individuals: human papilloma virus-induced squamous cell carcinoma and atypical hypertrophic herpes simplex virus. Keen consideration must be employed when determining the etiologic agent of anogenital lesions in HIV-infected individuals, particularly when surgical or oncological treatments are being considered. Clarification may require pathologic examination of tissue specimens, as seen with surgical excision in this case.